Kinematic analysis of kicking in young top-class soccer players - Juárez, D.; Mallo, J.; de Subijana, C. L.; Navarro, E. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM:The aim of this study was to describe the kinematic pattern of the kicking movement of young top-class soccer players focusing in examining the linear joint markers velocity of the leg kick and the segments angular position. METHODS: Maximal instep kicks performed by 21 young top-class soccer players (16.1±0.2 years) were analyzed using a three dimensional motion capture system. RESULTS: The ball was released at a mean velocity of 30.6±1.54 m/s. The maximum linear velocity of the hip (5.49±0.53 m/s), knee (10.89±0.63 m/s), ankle (19.36±0.96 m/s) and toe (24.59±1.33 m/s) joint markers were achieved consecutively during the kick, representing a typical proximal to distal kinetic chain. Significant (P<0.01) differences in the arms, trunk, thigh, shank and foot segments angular positions were found among the instant times in which the key events took place, determined by the maximum velocity of the hip (T1), knee (T2), ankle (T3) and toe (T4) joint markers (except between T3 and T4). This fact indicates that the instant time when each joint marker reached its maximum velocity implied different positions of the body segments. CONCLUSION: The results of this study provide additional data about the kicking biomechanics of young top-class soccer players. This information should be taken in consideration by coaches that train young soccer players.